Workplace Intervention for Reducing Sitting Time in Sedentary Workers: Protocol for a Pilot Study Using the Behavior Change Wheel - Ojo, Samson O.; Bailey, Daniel P.; Chater, Angel M.; Hewson, David J. (Frontiers in Public Health, 2022)
The workplace is a major contributor to excessive sitting in office workers. There are a wide array of adverse effects of high volumes of sitting time, including an increased risk of type 2 diabetes and depression. Active workstations can be used in effective interventions to decrease workplace sitting. However, there are a lack of interventions that have been developed using a systematic process that is informed by participant needs and a framework for identifying the most appropriate content for the intervention. Applying these methods could increase adherence and potential effectiveness of the intervention. Therefore, the purpose of this pilot study is to examine the feasibility, acceptability, and effects of a tailored workplace intervention to reduce and break up sitting in office workers that has been developed using the Behaviour Change Wheel and the APEASE (Acceptability, Practicability, Effectiveness/cost-effectiveness, Affordability, Safety/side-effects, Equity) criteria. This paper reports the protocol for this study that is currently ongoing. Participants will be cluster-randomised (by offices) to control and intervention groups. The evaluation of the intervention includes determining feasibility by assessing participant recruitment, retention and data completion rates. Adherence to the intervention will be assessed based on daily sitting and standing time relative to guidelines provided to participants as part of the intervention. Outcome measures also include productivity measured using Ecological Momentary Assessment, absenteeism, presenteeism, cardiometabolic risk markers, and wellbeing. The findings of this study will inform the effective design and implementation of interventions for reducing and breaking up sitting in office workers.